Advances in Manufacturing II Volume 1 - Solutions for Industry 4.0 - Trojanowska, Justyna; Ciszak, Olaf.; Machado, José Mendes; Pavlenko, Ivan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers a variety of topics related to the Industry 4.0 concept, with a special emphasis on the efficiency of production processes and innovative solutions for smart factories. It describes tools supporting this concept in both the mechanical engineering and biomedical engineering field. The content is based on papers presented at the 6th International Scientific-Technical Conference MANUFACTURING 2019, held on 19-22 May 2019, in Poznan, Poland. Virtual reality, simulation of manufacturing systems, additive manufacturing, big data analysis, automation and application of artificial intelligence, as well as economic and social issues related to the integration of those technologies are just some of the topics discussed here. All in all, the book offers a timely and practice-oriented reference guide for researchers and practitioners, and is expected to foster better communication and closer cooperation between universities and their business and industrial partners.
Digitization and Intangible Assets in Manufacturing Industries -- Human-Organization Relation in Perspective of Industry 4.0 -- Edge Computing Technologies as a Crucial Factor of Successful Industry 4.0 growth. The Case of Live Video Data Streaming -- Model Proposal to Evaluate the Quality of a Production Planning and Control Software in an Industrial Context -- Increasing the Production Productivity with Artificial Bee Colony Optimization Method -- Comparison of NC Data Preparation Ways for Drawingless Production -- Artificial Hand Controlled by a Glove with a Force Feedback.
Keywords: Cooperating objects (Computer systems).; Manufactures; Control engineering; Robotics; Automation; Computer-aided engineering; Cyber-Physical Systems; Machines, Tools, Processes; Control, Robotics, Automation; Computer-Aided Engineering (CAD, CAE) and Design